How Digital Payment and Online Marketing Strategies affect Consumer Experience in the Culinary Industry? - Rachmawaty Kadir; Andi Naila Quin Azisah Alisyahbana2; Nursinah Amrullah; Ririn Mardhani Syakur; Amraeni Amraeni (Indonesian Journal of Business and Entrepreneurship Research, 2024)
This study aims to analyze the impact of digital payment and online marketing strategies on the customer experience in the food industry, with a focus on the company "Kaku Food." As digital technology increasingly shapes the food industry, Kaku Food has effectively leveraged these advancements to enhance service quality and customer interaction. The research method involved a survey of 57 respondents who were Kaku Food customers. The results of the analysis show that both digital payment and online marketing have a significant impact on the customer experience. Specifically, the implementation of digital payment methods, such as e-money and e-wallets, has led to faster transactions and reduced wait times, contributing to higher customer satisfaction. Moreover, creative online marketing strategies, particularly through social media and collaborations with culinary influencers, have proven effective in reaching a digitally active audience, especially young people. The coefficient of determination indicates that 64.2% of the variation in customer experience can be explained by these two variables. The regression results reveal that while both digital payment and online marketing have positive and significant coefficients against customer experience, online marketing exerts a greater influence. This study provides valuable insights for Kaku Food management to formulate effective marketing strategies and payment systems, ultimately enhancing customer satisfaction and fostering greater loyalty.